“RAMBO” In Tonga: Video Films and Cultural Resistance in the Tongan Islands (South Pacific) - Gailey, Christine Ward (Culture, 1989)
Video films and VCR’s have widespread popularity in the kingdom of Tonga (South Pacific). Based on field research in urban neighbourhoods, the author argues that local interpretations of videos can vary markedly from dominant meanings, but at times parallel them. Discussion of the distribution, ownership, video genres available, and viewing patterns - as well as shifting land rights, cash income needs, and international labor migration - provides the context of audience interpretations. The basis for congruence or difference in interpretation is sought in local view of Tongan history and of changing socioeconomic conditions. The Tongan case has significance for contemporary debates about cultural hegemony and resistance in neocolonial developing countries.